2013
DOI: 10.1107/s0108270113017423
|View full text |Cite
|
Sign up to set email alerts
|

A new polymorph of bis(2-aminopyridinium) fumarate–fumaric acid (1/1) from powder X-ray diffraction

Abstract: A new polymorph of bis(2-aminopyridinium) fumarate-fumaric acid (1/1), 2C₅H₇N₂⁺∙C₄H₂O₄²⁻-·C₄H₄O₄, was obtained and its crystal structure determined by powder X-ray diffraction. The new polymorph (form II) crystallizes in the triclinic system (space group P-1), while the previous reported polymorph [form I; Ballabh, Trivedi, Dastidar & Suresh (2002). CrystEngComm, 4, 135-142; Büyükgüngör, Odabaşoğlu, Albayrak & Lönnecke (2004). Acta Cryst. C60, o470-o472] is monoclinic (space group P2₁/c). In both forms I and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In addition, the DDM refinement reveals that the molecular conformation of both the fumarate ion and fumaric acid in (II) is essentially nonplanar, with the angles between the planes through C atoms and CO 2 groups being 8.4 (6) and 15.7 7, respectively. The respective angles 3.8 (4) and 6.7 (4) resulting from the restrained Rietveld refinement by Dong et al (2013) were notably underestimated due to the planarity restraints imposed, presumably, by analogy with the singlecrystalline monoclinic polymorph of (II) where these angles did not exceed 5 . Evidently, the planarity restraints were excessive as the conformation of fumarate and fumaric acid molecules is flexible and the above discussed angles may well exceed 20 depending on the packing and hydrogen bonding (Sathya et al, 2013).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In addition, the DDM refinement reveals that the molecular conformation of both the fumarate ion and fumaric acid in (II) is essentially nonplanar, with the angles between the planes through C atoms and CO 2 groups being 8.4 (6) and 15.7 7, respectively. The respective angles 3.8 (4) and 6.7 (4) resulting from the restrained Rietveld refinement by Dong et al (2013) were notably underestimated due to the planarity restraints imposed, presumably, by analogy with the singlecrystalline monoclinic polymorph of (II) where these angles did not exceed 5 . Evidently, the planarity restraints were excessive as the conformation of fumarate and fumaric acid molecules is flexible and the above discussed angles may well exceed 20 depending on the packing and hydrogen bonding (Sathya et al, 2013).…”
Section: Resultsmentioning
confidence: 97%
“…In Fig. 6 and Table 3, the interatomic distances in (II) resulting from the unrestrained DDM refinement are compared with those obtained from an accurate single-crystal refinement of its monoclinic polymorph (Bü yü kgü ngö r et al, 2004) and a restrained Rietveld refinement on the same XRPD data with 77 geometric restraints per 56 variable parameters (Dong et al, 2013). Whereas the restraints were aimed, obviously, at improving the respective geometric parameters, the average deviation of distances from the singlecrystal data appeared to be half as large for the unrestrained DDM compared with the restrained Rietveld refinement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This motif is one of the 24 most frequently observed bimolecular cyclic hydrogenbonded motifs in organic crystal structures. In 2013 Dong et al [3] found the new polymorph of 2APF-F, which crystallized in triclinic system in centrosymmetric space group. In both polymorphs asymmetric units consist of one 2-aminopirydinium cation, half a fumaric acid molecule and half a fumarate dianion.…”
Section: Introductionmentioning
confidence: 99%